Answer:
Explanation:
We will use the reduction of order to solve this equation. At first, we need a solution of the homogeneus solution.
Consider the equation
We will assume that the solution is of the form
. If we plug this in the equation, we get
![Ae^(rx)(r^2+2r+1)=0](https://img.qammunity.org/2021/formulas/mathematics/college/cd9fpwzxszke9liutprjws6nt1bocuug4n.png)
Since the exponential function is a positive function, and A should be different to zero to have non trivial solutions, we get
![r^2+2r+1=0](https://img.qammunity.org/2021/formulas/mathematics/college/sa2b79x43ogfviopn5t060a9rx1b237y4v.png)
By using the quadratic formula, we get the solutions
![r= \frac{-2\pm \sqrt[]{4-4}}{2}=-1](https://img.qammunity.org/2021/formulas/mathematics/college/oq9xekiay13g2bjnafy3zymuhu22558re8.png)
So one solution of the homogeneus equation is of the form
. To use the reduction of order assume that
where
. We calculate the derivatives and plug it in the equation
![y' = v'y_h+y_h'v](https://img.qammunity.org/2021/formulas/mathematics/college/n27pyjwqc7rwmugnk57a9ca437efu0zcmh.png)
![y'' = v''y_h+v'y_h'+y_h'v'+y_h''v = v''y_h+2v'y_h+y_h''v](https://img.qammunity.org/2021/formulas/mathematics/college/zgfcxc0jwhr4s9kc93xjudm7opu99vupzf.png)
![(v''y_h+2v'y_h'+y_h''v)+2(v'y_h+y_h'v)+vy_h = 0](https://img.qammunity.org/2021/formulas/mathematics/college/99umixtjze89cl17kaxzj14a4obt3oy0hm.png)
If we rearrange the equation we get
![v''y_h+(2y_h'+2y_h)v'+v(y_h''+2y_h'+y_h)=0](https://img.qammunity.org/2021/formulas/mathematics/college/co0d91vzzfsnhsootbv86egdr7tkh4nrnr.png)
Since
is a solution of the homogeneus equation we get
![v''y_h+(2y_h'+2y_h)v'=0](https://img.qammunity.org/2021/formulas/mathematics/college/f1d6lfb7tja3xah4m2d8lj0byu1tmrd3ni.png)
If we take w = v', then w' = v''. So, in this case the equation becomes
![w'y_h+(2y_h'+2y_h)w=0](https://img.qammunity.org/2021/formulas/mathematics/college/j9qncz5jsow5h2623sra95imapykq30dhn.png)
Note that
so
. Since
cannot be zero, this implies
w' =0. Then, w = K (a constant). Then v' = K. So v=Kx+D where D is a constant.
So, we get that the general solution is
where C, F are constants.